2019
DOI: 10.1101/720599
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Theranostic cranial implant for hyperspectral light delivery and microcirculation imaging without scalp removal

Abstract: Light based techniques for imaging, diagnosing and treating the brain have become widespread clinical tools, but application of these techniques is limited by optical attenuation in the scalp and skull. This optical attenuation reduces the achievable spatial resolution, precluding the visualization of small features such as brain microvessels. The goal of this study was to assess a strategy for providing ongoing optical access to the brain without the need for repeated craniectomy or retraction of the scalp. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…However, transgranular fractures will occur when numerous dislocations are formed in the crystal grains . Our previous studies indicated that the CAPAD-processed 8YSZ disc had a hardness of 13.2 ± 0.1 GPa, whereas the SPS-processed 8YSZ_P disc showed a similar hardness of 13.9 ± 0.7 GPa, which suggested that the CAPAD and SPS processes may have limited effects on the hardness of YSZ discs.…”
Section: Discussionmentioning
confidence: 98%
“…However, transgranular fractures will occur when numerous dislocations are formed in the crystal grains . Our previous studies indicated that the CAPAD-processed 8YSZ disc had a hardness of 13.2 ± 0.1 GPa, whereas the SPS-processed 8YSZ_P disc showed a similar hardness of 13.9 ± 0.7 GPa, which suggested that the CAPAD and SPS processes may have limited effects on the hardness of YSZ discs.…”
Section: Discussionmentioning
confidence: 98%
“…The skull and OCS scattering both disorder the speckle pattern that was created by the brain hemodynamics. The reduction in border sharpness of the vessels imaged through the intact skull vs. OCS + implant suggests that the skull has a higher blurring effect [48].…”
Section: Theranostic Cranial Implant For Hyperspectral Light Delivery and Microcirculation Imagingmentioning
confidence: 99%
“…The noninvasive interactions with tissue of photons within this energy range have been used in numerous approaches to assess brain health and treat its diseases. The application of transparent cranial implants holds the transformative potential for facilitating the diagnosis and treatment of a wide variety of brain pathologies and neurological disorders [48]. Implementing this implant in the current cranial prostheses or a separate implantation of "Window to the Brain" (WttB) implant (e.g.…”
Section: Theranostic Cranial Implant For Hyperspectral Light Delivery and Microcirculation Imagingmentioning
confidence: 99%
See 1 more Smart Citation